INDUCTION AND IDENTIFICATION OF AUTOTETRAPLOIDS IN PEARL MILLET (Pennisetum glaucum L) FOR ITS UTILIZATION IN PEARL MILLET NAPIER GRASS BREEDING - L. SWATHI; C. BABU; K. IYANAR; U. SIVAKUMAR; A.J. PRABAKARAN (The Bioscan, 2020)
The present investigation was carried out to induce chromosomal doubling in pearl millet variety CO 8. Twenty five seeds for each treatment were exposed to colchicine @ of 0.00, 0.05, 0.06, 0.07, 0.08, 0.09 and 1.0 per cent for different durations of 6, 8, 12 and 24 hrs, and the highest germination and survival per cent was recorded in 0.05% for 6 hrs treatment with a range of 27.0 to 56.0 and, 1.5 to 19.4 per cent, respectively. Preliminary screening was based on stomatal measurements and maximum mean stomatal size was (51.7 ± 4.6) in the mutant with 0.07% for 8 hrs duration treatment. Two major variants were identified and the meiotic chromosome number of one of the variant (Pl. No. 36) was 24, against its control with 14 chromosomes. Bivalents and laggards were observed. The pollen fertility and seed set of this mutant were 53% and 5%, respectively. The values of the typical polyploidy traits of this mutant were higher than the control. The other variant was found to have bristled panicle (Pl. No. 36). Therefore, colchicines can be efficiently utilized for chromosomal doubling, however a very large population has to be maintained to isolate desirable mutants.